2023
DOI: 10.21203/rs.3.rs-3108281/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of an early alert model for pandemic situations in Germany

Abstract: The COVID-19 pandemic has pointed out the need for new technical approaches to increase the preparedness of healthcare systems. One important measure is to develop innovative early warning systems. Along those lines we developed a machine learning (ML) approach using Google Trends and Twitter data for Germany. As a use case we evaluated our models using COVID-19 surveillance data between March 2020 and June 2022. In conclusion we found that a long-short-term memory (LSTM) jointly trained on COVID-19 symptoms r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…As metadata, we incorporated data from Google Trends following Wang et al [24]. First, we identified the 20 top symptoms of COVID-19 which were used as search terms in Google Trends.…”
Section: Metadatamentioning
confidence: 99%
See 2 more Smart Citations
“…As metadata, we incorporated data from Google Trends following Wang et al [24]. First, we identified the 20 top symptoms of COVID-19 which were used as search terms in Google Trends.…”
Section: Metadatamentioning
confidence: 99%
“…Our above-described modeling approaches used only surveillance data, their forecasts, and estimated prediction performances as input for the base models and meta-model, respectively. In our previous publication, we showed that social media data is not only correlated with surveillance data but can also be used to forecast up-and downtrends of pandemic waves [24]. Therefore, we wanted to test if the inclusion of social media data or further metadata could improve the prediction performance of the meta-model.…”
Section: Inclusion Of Metadatamentioning
confidence: 99%
See 1 more Smart Citation